Examination of Drosophila eye development with third harmonic generation microscopy - Karunendiran, Abiramy (Biomed Opt Express, 2017)
Third harmonic generation (THG) microscopy can exploit endogenous harmonophores such as pigment macromolecules for enhanced image contrast, and therefore can be used without exogenous contrast agents. Previous studies have established that carotenoid compounds are ideal harmonophores for THG microscopy; we therefore sought to determine whether THG from endogenous carotenoid-derived compounds, such as retinal in photoreceptor cells, could serve as a new label-free method for developmental studies. Here we study the development of the pupal eye in Drosophila melanogaster and determine the localization of rhodopsin using THG microscopy technique. Additionally, by altering the chromophore or the opsin protein we were able to detect changes in both the retinal distribution morphology and in THG intensity age-dependent profiles. These results demonstrate that THG microscopy can be used to detect altered photoreceptor development and may be useful in clinically relevant conditions associated with photoreceptor degeneration.